The Effects of Contact With Nature During Outdoor Environmental Education on Students’ Wellbeing, Connectedness to Nature and Pro-sociality - Pirchio, Sabine; Passiatore, Ylenia; Panno, Angelo; Cipparone, Maurilio; Carrus, Giuseppe (Frontiers in Psychology, 2021)
Experiences of contact with nature in school education might be beneficial for promoting ecological lifestyles and the wellbeing of children, families and teachers. Many theories and empirical evidence on restorative environments, as well as on the foundations of classical pedagogical approaches, recognize the value of the direct experience with natural elements, and the related psychological and educational outcomes (e.g., positive emotions, autonomy, self-efficacy, empathy). In this work we present two studies focusing on the contact with nature in outdoor education interventions with primary and secondary school students in Italy. A questionnaire measuring connectedness to nature, psycho-physical wellbeing, pro environmental attitudes, students’ life satisfaction, prosocial behaviour, empathy and anxiety was completed before and after the education program by the participants to the intervention group and by students of a control group. The students in the intervention groups (154 in study 1 and 170 in study 2) participated in environmental education programs consisting in guided activities in contact with the nature during 4 visits in one of two natural protected areas. The students in the control groups (253 in study 1 and 168 in study 2) attended the same schools as the intervention group but they were not involved in the environmental education program. The students in both the groups completed the questionnaire in the same weeks of the year. Findings show that taking part to the outdoor education program has positive outcomes on psycho-physical wellbeing, on connectedness to nature and on prosocial behaviour of students in the intervention group, compared to the control group. The implications related to the effectiveness of outdoor education interventions and future directions of research and practice in environmental psychology and education are discussed.